Molecular Biological Investigation of the Effect of Sumac Extract on Protein Synthesis and Development of Saccharomyces cerevisiae - Gok, Ozlem; Beyaz, Seda; Aslan, Abdullah (Progress in Nutrition, 2022)
Study objective: Sumac is a plant that is widely used for various purposes such as industrial, pharmaceutical and nutritional applications. Adding it to food or water as a natural preservative can have a beneficial effect on human health. It has biological activities such as anti-bacterial, anti-fungal and anti-oxidant. In this study, the effect of sumac plant on oxidative damage in S. cerevisiae culture caused by copper chloride (CuCl2) was investigated. Methods: In this study 4 groups were formed. Groups; Group (1): Control group; Group (2): Sumac group (10%); Group (3): Copper chloride (CuCl2) group (10 mM); Group (4): Sumac (10%) + Copper chloride (CuCl2) (10 mM) group. S. cerevisiae cultures were developed at 30°C for 1 hour, 3 hours, 5 hours and 24 hours. Cell growth, lipid peroxidation, MDA (malondialdehyde) analyzes, glutathione (GSH) levels and catalase (CAT) activities were determined by spectrophotometer. Total protein changes were determined by SDS-PAGE electrophoresis and calculated by the Lowry method. Results: According to the results obtained; Sumac plant extract which added to S. cerevisiae cultures increased cell growth (1, 3, 5 and 24 hours), total protein synthesis (1 hour, 3 hours, 5 hours and 24 hours), GSH levels (24 hours) and catalase activities (24 hours), decreases the MDA level (24 hours). Conclusions: These results show that sumac plant extract reduces oxidative damage in S. cerevisiae culture, promotes protein synthesis and has a protective effect to increase cell growth.